In vitro synthesis and processing of a maize chloroplast transcript encoded by the ribulose 1,5-bisphosphate carboxylase large subunit gene. - Hanley-Bowdoin, L (1985)
The large subunit gene (rbcL) of ribulose 1,5-bisphosphate carboxylase was transcribed in vitro by using maize and pea chloroplast extracts and a cloned plastid DNA template containing 172 base pairs (bp) of the maize rbcL protein-coding region and 791 bp of upstream sequences. Three major in vitro RNA species were synthesized which correspond to in vivo maize rbcL RNAs with 5' termini positioned 300, 100 to 105, and 63 nucleotides upstream of the protein-coding region. A deletion of 109 bp, including the "-300" 5' end (the 5' end at position -300), depressed all rbcL transcription in vitro. A plasmid DNA containing this 109-bp fragment was sufficient to direct correct transcription initiation in vitro. A cloned template, containing 191 bp of plastid DNA which includes the -105 and -63 rbcL termini, did not support transcription in vitro. Exogenously added -300 RNA could be converted to the -63 transcript by maize chloroplast extract. These results established that the -300 RNA is the primary maize rbcL transcript, the -63 RNA is a processed form of the -300 transcript, and synthesis of the -105 RNA is dependent on the -300 region. The promoter for the maize rbcL gene is located within the 109 bp flanking the -300 site. Mutagenesis of the 109-bp chloroplast sequence 11 bp upstream of the -300 transcription initiation site reduced rbcL promoter activity in vitro.